Extraction of proteins secreted by the phytopathogen Macrophomina phaseolina: Selection of an efficient method that includes stimulation with its host tissue - Benegas, Andrea (2022)
The globally distributed necrotrophic fungus Macrophomina phaseolina is the causal agent of economically important crop diseases such as soybean charcoal rot. This fungus secretes a wide variety of proteins and metabolites that allow it to invade the plant and initiate the infection process. The role of fungi secreted proteins with hydrolytic activity in the infection process has been extensively studied; proteins without enzymatic activity could also play an important role in this process. The analysis of total proteins would allow to broaden the knowledge about this pathogen and establish more efficient strategies for its control. The objective of the present work was to evaluate three methods for the extraction of proteins secreted by M. phaseolina. The fungus was grown in potato dextrose broth (PDB) and Czapek-Dox (CZP) with and without soybean leaf supplementation. Proteins were extracted from the lyophilized filtrate of PDB medium using three extraction methods and analyzed by SDS-PAGE. The protein precipitation with trichloroacetic acid in acetone was selected because it showed a better resolution of the protein profile. The filtrate of M. phaseolina grown in PDB supplemented with soybean (MpPDBs) presented the highest yield of protein extraction of secreted proteins among all conditions evaluated. The protein profiles of PDB medium with and without supplementation showed seven differential bands, one of the specific, detected in MpPDBs. These results constitute a basis for studies on the implication of proteins secreted by the fungus in the infection process.